Measurement of Peak Systolic Velocities and End Diastolic Velocities of Common Carotid, Internal Carotid and Vertebral Arteries of Healthy Adult Subjects by Duplex Colour Doppler Sonography : A Study of 100 Cases - Chowdhury, Jamil Haider; Saha, Krishna Kishore (IAHS Medical Journal, 2022)
Background : Duplex Colour Doppler Sonography is a well-accepted non invasive means for diagnosis and evaluation of carotid and vertebral artery disease. As these arteries are the main supply of brain, determination of their percentage of stenosis accurately is very much important. The accuracy of measurement of percent stenosis using doppler technique depends significantly on measured blood flow velocities in these arteries. As a result, a normal reference value of peak systolic velocity and end diastolic velocity for these arteries are needed upon which the calculation of percentage stenosis depends. At this context, this study was done with the following objectives: To measure Peak Systolic Velocities and End Diastolic Velocities of common carotid, internal carotid and vertebral arteries of healthy adult subjects by duplex colour doppler sonography, to estimate the velocity difference in extra - cranial neck vessels of right and left side and to observe the velocity difference between males and females. Materials and methods : This cross-sectional study was conducted among Bangladeshi healthy adult subjects in the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU) from January2009 to December 2009. 100 Bangladeshi healthy adult subjects were selected which included 50 males and 50 females. All the subjects underwent duplex colour doppler scanning of their Common Carotid Artery (CCA) Internal Carotid Artery (ICA) and Vertebral Arteries (VA) on both sides. Peak Systolic Velocities (PSV) and End-Diastolic Velocities (EDV) of the above arteries on both sides were recorded for analysis. Results: In case of male subjects, mean PSV of common carotid, internal carotid and vertebral arteries on the right side are 66, 57 and 30 cm/sec and on the left side are 72, 58 and 32 cm/sec consecutively. In the case of male subjects, mean EDV of common carotid, internal carotid and vertebral arteries on the right side are 19, 16 and 10 cm/sec and on the left side are 21, 21 and 15 cm/sec consecutively. In case of female subjects, mean PSV of common carotid, internal carotid and vertebral arteries on the right side are 62, 57 and 29 cm/sec and on the left side are 65, 57 and 30 cm/sec consecutively. In the case of female subjects, mean EDV of common carotid, internal carotid and vertebral arteries on the right side are 20, 19 and 14 cm/sec and on the left side are 21,17 and 14 cm/sec consecutively. Conclusion: From this study, we have provided reference values of peak systolic velocity and end diastolic velocity for these arteries (CCA, ICA & VA) in Bangladeshi population. IAHS Medical Journal Vol 4(1), June 2021; 17-21